RAILROAD CROSSINGS AND TRAFFIC RULES ON THEM (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2024)
Railroad crossings represent critical points of interaction between rail and road transport systems. Ensuring safety at these intersections is paramount to reducing accidents and fatalities. This article explores the various types of railroad crossings, the traffic rules associated with them, and the strategies implemented to enhance safety. The study delves into the effectiveness of current safety measures and offers recommendations for improvements based on statistical analysis and case studies.